Understanding the barriers and facilitators to delivering peer support effectively in England: a qualitative interview study - Una Foye; Natasha Lyons; Prisha Shah; Lizzie Mitchell; Karen Machin; Beverley Chipp; Stephen Jeffreys; Tamar Jeynes; Karen Persaud; Vicky Nicholls; Ruth E. Cooper; Andrew Grundy; et al. (BMC Psychiatry)
Abstract Background Peer support roles within mental health services are rapidly increasing in number and scope in the UK and internationally. This paper explores the facilitators and barriers to delivering peer support effectively, as experienced by Peer Support Workers (PSWs) in a range of services and settings. Methods We conducted semi-structured qualitative interviews with paid mental health PSWs working across a range of settings in England. We took a collaborative, participatory approach. Interviews were carried out by researchers with experience of living with and/or supporting others with mental health conditions, and for some having experience delivering peer support themselves, and data were analysed using methods guided by general principles of thematic analysis. Results We interviewed 35 PSWs with a range of roles that spanned a range of mental health areas, and regions. Overarching facilitators and barriers were identified including the need for roles to have flexibility with some structure and boundaries; the need for support, supervision and training to ensure PSWs are skilled in delivering the unique elements of their job; the importance of working with a strong team and leaders who support and value PSW; the complexity of working where there are tensions between the flexibility of PSW and the structures of existing healthcare systems, as well as the systemic factors such as funding, pay and progression can have an effect both on the personal experience of PSWs and on the value placed on PSWs in the wider organisation. Conclusion Our findings highlight the complexity of peer support work and PSW roles, with a variety both of facilitators allowing them to carry out roles effectively and the barriers to doing so. As PSWs numbers and the scope of their roles increase, awareness of barriers and facilitators needs to inform PSW job roles, support systems and integration into teams and systems.